REACTIONS OF MERCURIC ACETATE WITH PENTACARBONYLIRON IN ALCOHOLS - CRYSTAL AND MOLECULAR-STRUCTURES OF HG[FE(COOR)(CO)(4)](2) (R=CH3, C2H5) - Mauro, A. E.; Neto, VAD; ZAMIAN, JR; Santos, RHD; Gambardella, MTD; LECHAT, JR; Rechenberg, H. R. (Elsevier B.V., 1994)
Reactions of Hg(CH3COO)(2) with [Fe(CO)(5)] in MeOH and EtOH lead to the compounds Hg[Fe(COOR)(CO)(4)](2) (I for R = CH3 and II for R = C2H5). Crystals of I are triclinic, P (1) over bar, with a = 6.272(2), b = 6.441(3), c = 11.703(4) Angstrom, a = 92.94(3)degrees, beta = 103.77(3)degrees, gamma = 96.10(2)degrees, and Z = 1. Crystals of II are tetragonal, I4(1)/a, with a = 17.906(3) Angstrom, c = 12.756(2) Angstrom, and Z = 8. The geometry around Hg is linear for compound I and approximately linear for compound II. The Hg-Fe distances are 2.5716(8) and 2.575(4) Angstrom for compounds I and II, respectively. The geometry around the Fe in both compounds is approximately octahedral. The carboalkoxy group is cis to Hg in both compounds with Fe-C distances equal to 2.034(6) and 2.05(4) Angstrom for compounds I and II, respectively.
Keywords: IRON; MERCURY; CARBONYL; CRYSTAL STRUCTURE; INFRARED SPECTROSCOPY; MOSSBAUER SPECTROSCOPY